CONTRIBUTION OF INCENTIVES ON THE PERFORMANCE OF HEALTH WORKERS IN BUKEDEA HEALTH CENTER IV - BYAKIKA MIRAM (My University, 2024)
Abstract Improvement of health has become a global commitment where governments and other development partners have all risen to ensure its attainment. This study sought to establish the influence of incentives on the performance of health workers in Bukedea health center 1V. The key predictors to employee performance were ; the role of monetary incentives in motivating health workers' performance, the role of support supervision in motivating health workers' performance and the challenges Bukedea health sector faces in motivating health workers in Bukedea Health center IV, The Methods used were drawn from both quantitative and qualitative approaches. Descriptive and case study research designs were used to come up with qualitative and quantitative data from the 60 respondents who were either health workers deployed in Bukedea health centre 1V or politicians serving the supervisory role in Bukedea district local government. A purposive and simple random sampling technique was used to identify the respondents. Purposive random sampling was used to get the actual respondents to be interviewed. Results; Using thematic analysis, the researcher came up with the following findings: The employer provides monetary incentives to the health workers however the employees feel the financial incentive is low and has affected their performance. 74% of the respondents emphasized that monetary incentives have not increased efficiency and improved their customer service 78% also responded that monetary incentives have not led employee satisfaction. As for support supervision, 59% of the nurses agreed that they receive support supervision, while 29% dis-agreed. Of those who disagreed, they were asked to explain why they were not getting that support supervision, their responses were; lack of recruitment of senior cadres, some supervisors have retired, too much workload from supervisors. The concluded that monetary incentives given to health workers in Bukedea district are very limited, There is low support supervision given to lower cadres, supports supervision in principle is a necessary and a very important tool that needs to be promoted in the medical fraternity.The power holders in the ministry of health and Bukedea district local government need to come out and try to create and consistently strengthen a good motivation environment for health workers, but most especially the lower cadres.